2021
DOI: 10.35848/1347-4065/ac3e17
|View full text |Cite
|
Sign up to set email alerts
|

Plan-view TEM observation of a single-domain κ-Ga2O3 thin film grown on ε-GaFeO3 substrate using GaCl3 precursor by mist chemical vapor deposition

Abstract: We demonstrated the growth of a single-domain κ-Ga2O3 thin film on ε-GaFeO3 by using an organic-free compound as a precursor for mist chemical vapor deposition. X-ray diffraction analysis revealed that an 87-nm-thick κ-Ga2O3 thin film was grown almost coherently with slight lattice relaxation. The surface morphology of the κ-Ga2O3 thin film exhibited a step-terrace structure without island growth. Furthermore, plan-view TEM observations revealed that the κ-Ga2O3 thin film grown on ε-GaFeO3 had a single domain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The presence of these rotational domains initially leads to them being incorrectly assigned to the hexagonal symmetry and group symmetry of P63mc, and regarding the material as ε-Ga 2 O 3 [ 25 ] instead of orthorhombic Pna21 κ-Ga 2 O 3 , which is correct. Thus, although a growth of single-domain films has been reported [ 34 ], in most cases, κ-Ga 2 O 3 can be considered to be a nanocrystalline material. The boundaries between these rotational domains present an obstacle to the current flow in the growth plane and, for a long time, have prevented the research of the electrical properties of κ-Ga 2 O 3 films; however, more recently, heterostructures and quantum wells of κ-(Al x Ga 1−x ) 2 O 3 /κ-Ga 2 O 3 with different Al mole fractions and hence different band structures have been demonstrated, and vertical NiO/κ-Ga 2 O 3 structures have been successfully fabricated by pulsed laser deposition [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these rotational domains initially leads to them being incorrectly assigned to the hexagonal symmetry and group symmetry of P63mc, and regarding the material as ε-Ga 2 O 3 [ 25 ] instead of orthorhombic Pna21 κ-Ga 2 O 3 , which is correct. Thus, although a growth of single-domain films has been reported [ 34 ], in most cases, κ-Ga 2 O 3 can be considered to be a nanocrystalline material. The boundaries between these rotational domains present an obstacle to the current flow in the growth plane and, for a long time, have prevented the research of the electrical properties of κ-Ga 2 O 3 films; however, more recently, heterostructures and quantum wells of κ-(Al x Ga 1−x ) 2 O 3 /κ-Ga 2 O 3 with different Al mole fractions and hence different band structures have been demonstrated, and vertical NiO/κ-Ga 2 O 3 structures have been successfully fabricated by pulsed laser deposition [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…This major disadvantage impairing the practical use of κ-Ga 2 O 3 -based structures and devices was partly overcome in [ 19 ] by employing ELOG growth on sapphire substrates masked with thin TiO 2 and patterned with either stripes or dots of SiO 2 ; this facilitated the formation of single-domain κ-Ga 2 O 3 films with good crystalline quality using HVPE. In addition, the authors of [ 32 , 34 ] were able to prepare single-domain κ-Ga 2 O 3 films using mist CVD growth on the ε-GaFeO 3 substrate. However, neither work detailed the electrical characterization of the κ-Ga 2 O 3 films grown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is nothing special about the occurrence of rotational domains using a (−201) β-Ga 2 O 3 substrate. Recently, it has been demonstrated that almost lattice-matched ε-GaFeO 3 (001) substrates with κ-Ga 2 O 3 36,37 and the lateral overgrowth on c -plane sapphire substrates 38 prevent the occurrence of this rotational domain. However, the origins of the peaks at around −114°, −72°, 68°, and 108° indicated by blue triangles in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, until now, some works indicate the possibility of the existence of pure ε-phase [12]. Despite the ongoing debate about the real structure of the considered phase, most scientific groups tend to consider the phase as composed of 3-fold rotational orthorhombic domains with disordered domain boundaries [10,11,13,14]; the single-domain orthorhombic structure of this phase has been recently demonstrated [3,15]. Therefore, in this work, we will consider this phase as κ-Ga2O3 with the orthorhombic crystal structure Pna21.…”
Section: Introductionmentioning
confidence: 99%